Thermal upgrades of existing homes in Germany: The building code, subsidies, and economic efficiency - Ray Galvin (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2009)
One of the cheapest ways to reduce CO2 emissions is thermal renovation of existing homes. Germany is a world leader in this project, with a strict building code, generous state subsidies, and an advanced renovation infrastructure. The effects of its policies are explored here in the light of progressive tightening of the building code, and the strict criteria for subsidies. Data on costs and outcomes of residential building renovations are presented from published reports on renovation projects, and cross-checked with projects investigated directly. Comparisons are made in terms of euros invested for every kilowatt-hour of heating energy saved over the lifetime of the renovations, for standards ranging from 150 (the lowest standard) to 15 (the highest) kilowatt-hours of primary energy use per square metre of floor area per year. It is found that the lowest standard is an order of magnitude more cost-effective than the highest, in terms of both energy saved per euro invested, and return on investment over the lifetime of the renovations, regardless of fuel prices. It is argued that this throws into question Germanys policy of progressively regulating for higher renovation standards, and offering subsidies only for projects that go beyond the minimum standard.
Keywords: 330; thermal refits; climate change mitigation; German CO2 policy; energy efficiency; Klimaschutz; Wohnungsbauinvestition; Wärmeenergie; Subvention; Baurecht; Deutschland